The Implementation of Guided Discovery Learning Model Based on Experiments toward Science Process Skills - Nurlina Nurlina (Jurnal Pendidikan Fisika, 2019)
This study aims to determine (1) science process skills students in class XI IPA 3 Pamboang 1 Public High School before being taught using a guided discovery learning model (2) science process skills students in class XI IPA 3 Pamboang 1 Public High School after being taught using a guided discovery learning model(3) science process skills students in class XI IPA 3 Pamboang 1 Public High School before and after being taught using a guided discovery learning model. This type of research is pre-experimental research with design The One group pretest – posttest design which involves independent variable namely the learning model guided discovery and the dependent variable is science process skills. The subjects of the study population were students of class XI IPA of SMA Negeri 1 Pamboang in the school year 2018/2019 which consists of 3 classes with selected samples random sampling (random class) so that it is obtained in class XI IPA 3. The results showed that the pretest of students obtained an average score of science process skills of 15.65. With a standard deviation of 4.95. While the posttest obtained an average score of 20.90 with a standard deviation of 4.62 and the average score of the normalized gain test is 0.36. So it can be concluded that the science process skills of students increase in the medium category after being applied to the Guided Discovery learning model.Keywords: Learners, Guided Discovery, Science Process SkillsPenelitian ini bertujuan untuk mengetahui (1) keterampilan proses sains peserta didik kelas XI IPA 3 SMA Negeri 1 Pamboang sebelum diajarkan menggunakan model pembelajaran discovery terbimbing (2) keterampilan proses sains peserta didik kelas XI IPA 3 SMA Negeri 1 Pamboang setelah diajarkan menggunakan model pembelajaran discovery terbimbing (3) keterampilan proses sains peserta didik kelas XI IPA 3 SMA Negeri 1 Pamboang sebelum dan setelah diajar dengan model pembelajaran Discovery Terbimbing. Jenis penelitian ini adalah penelitian pra eksperimen dengan desain The One group pretest – posttest design yang melibatkan variabel bebas yaitu model pembelajaran discovery terbimbing dan variabel terikat yaitu keterampilan proses sains. Subyek populasi penelitian  adalah peserta didik kelas XI IPA SMA Negeri 1 Pamboang tahun ajaran 2018/2019 yang terdiri dari 3 kelas dengan sampel di pilih secara random sampling (kelas acak) sehingga diperoleh kelas XI IPA 3. Hasil penelitian menunjukkan pada pretest peserta didik memperoleh skor rata-rata keterampilan proses sains sebesar 15,65. Dengan standar deviasi sebesar 4,95. Sedangkan pada posttest diperoleh skor rata-rata  sebesar 20,90 dengan standar deviasi sebesar 4,62 dan skor rata-rata uji gain ternormalisasi sebesar 0,36. Sehingga dapat disimpulkan bahwa keterampilan proses sains peserta didik meningkat dalam kategori sedang setelah diterapkan model pembelajaran Discovery Terbimbing.Kata kunci: Peserta Didik, Discovery Terbimbing, Keterampilan Proses Sains